The impact of information technology management on the Algerian economic institutions in light of corporate governance - Mezhoud, Hichem; Kalleche, Meryem (Finance and Business Economies Review, 2020)
This study aims to highlight the importance of the role that IT management can play in Algerian economic institutions in the light of corporate governance. As a result of the integration between information technology and corporate governance, the concept of IT governance has emerged as IT governance in the economic environment has given great importance to the success of economic transactions , And the relationship between the application of corporate governance and IT governance, where IT governance is a part of corporate governance, and the study recommended that the benefits of applying S corporate governance in Algerian economic institutions